The Implementation of Public Communication Management Policy at Ministry of Energy and Mineral Resources: Implementasi Kebijakan Pengelolaan Komunikasi Publik di Kementerian Energi dan Sumber Daya Mineral: The Implementation - Thoriq Ramadani (Pusjar SKPP Lembaga Administrasi Negara, 2019)
Management of public communication plays significant role in a government. The implementation of well-made management of public communication can be a means to deliver government policies both as programs and achievements broadcasted to public. The purpose of this study was to determine the implementation of communication policy management at the Ministry of Energy and Mineral Resources (ESDM). The method used was a case study at the ESDM with analysis implementation by using used Edwards III model. Based on the analysis, it was found that the implementation of the public communication management policy at the Ministry of Energy and Mineral Resources was already underway, such as the availability of a planned public communication strategy, and indicators of success in the mass media which were not only numerous but also positive and neutral quality, so that negative coverage could be minimized. Besides, the support of Officials and Implementers, Standard Operating Procedures (SOP), and creative content through hashtags related to the Energy and Mineral Resources sector could also increase the social media followers. Keywords: Policy, Implementation, Communication Management, Public Communications Abstrak Pengelolaan komunikasi publik merupakan hal penting dalam sebuah pemerintahan. Implementasi kebijakan tentang pengelolaan komunikasi publik yang telah dibuat, sebagaimana pengelolaan komunikasi publik menjadi sarana penyampaian kebijakan Pemerintah, baik itu program maupun capaian yang disampaikan kepada masyarakat. Tujuan dari penelitian ini adalah untuk mengetahui implementasi kebijakan pengelolaan komunikasi publik di Kementerian Energi dan Sumber Daya Mineral (ESDM). Metode yang digunakan adalah studi kasus pada Kementerian ESDM dengan analisis implementasi kebijakan pengelolaan komunikasi publik dengan model Edwards III. Berdasarkan hasil analisa ditemukan bahwa implementasi kebijakan pengelolaan komunikasi publik di Kementerian ESDM sudah berjalan, seperti adanya strategi komunikasi publik yang terencana, indikator keberhasilan berupa pemberitaan di media massa yang tidak hanya banyak tapi juga kualitasnya yang positif dan netral, sehingga pemberitaan negatif dapat diminimalisir. Selain itu, dukungan Pejabat dan Pelaksana, Standard Operating Procedure (SOP), dan konten-konten kreatif melalui tanda pagar (tagar) yang terkait sektor ESDM dapat meningkatkan jumlah pengikut media sosial. Kata Kunci: Implementasi; Kebijakan; Pengelolaan Komunikasi; Komunikasi Publik